Influence of the Social Network on Married and Unmarried Older Adults' Mental Health. (18th September 2017) - Stokes, Jeffrey E; Moorman, Sara M
Abstract: Purpose of the Study: In later life, adults' social networks grow smaller through a combination of intentional selection and involuntary loss. This study examined whether older adults who lack a high-quality marriage compensate for this using support from other ties. We analyzed how relationships with family and friends are associated with depressive symptoms across multiple marital statuses. Design and Methods: Data from 3, 371 older adults who participated in the most recent wave of the National Social Life, Health, and Aging Project (NSHAP) were analyzed using analysis of variance (ANOVA) and ordinary least squares (OLS) regression. Results: Individuals in high-quality marriages experienced fewer depressive symptoms than the widowed, never married, divorced/separated, and those in lower-quality marriages. Older adults' perceived family support, family strain, and friend strain were all significantly associated with depressive symptoms. The only difference in these effects according to marital status was for perceived family support, which was strongest for the never married. Implications: The never married may depend more on family and friends than the previously or unhappily married. Any compensation efforts among the latter failed to reduce depressive symptoms relative to happily married others. Older adults in high-quality marriages benefit from their marital relationship, and also benefit from supportive family and friend ties.